Strategic Talent Management Practices for Enhancing Employee Retention in Competitive Work Environments - Muhammad Syafri; Danan Wuryanto Pramono; Ade Suhara (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
High employee turnover remains a significant challenge for organizations operating in competitive work environments, leading to concerns over productivity, workforce stability, and long-term sustainability. Strategic talent management is considered a crucial approach for organizations seeking to retain skilled employees and enhance organizational performance. This study aims to explore talent management practices that support employee retention in competitive industries by examining underlying factors contributing to turnover and strategies used to maintain employee commitment. This research employs a library-based methodology that relies on secondary data from books, journal articles, research reports, and academic publications related to employee retention, strategic talent management, and competitive work environments. Data were analyzed using content analysis to identify key themes, patterns, and relationships across the literature. The findings reveal that effective recruitment, continuous employee development, succession planning, competitive compensation, supportive organizational culture, work-life balance, and clear career development opportunities are essential in strengthening employee loyalty and reducing turnover. Additionally, organizations must balance high performance expectations with well-structured support systems to prevent burnout. The study highlights the importance of strategically integrating strategic talent management practices with initiatives that prioritize employee well-being to maintain retention and sustain competitive advantage.